The Effects of Job Insecurity on Job Performance among Banking Employees: The Mediating Role of Work Engagement - Batool, Iram; Nawaz, Sadaf (South Asian Journal of Social Sciences and Humanities, 2021)
Based on the assumption that the construct of job insecurity should as a major influencing factor for workers’ job performance in the evaluation model and its often given a consideration whenever the objective is determining factors that influence employee performance, including the role of work engagement of work engagement of workers employees. Present study aimed to explore the effects of job insecurity on job performance. It was further aimed to find out the role of work engagement as a mediator among bank employees. To advance our line of theoretical reasoning, we elicit responses from a total of Four hundred 400 employees (Male= 331, Females=69) working in different banks aged between 22 to 44 years randomly selected bankers in 15 Public and private banks from two Pakistani cities. Job insecurity scale by Francis & Barling. (2005), Work engagement by Schaufeli et al. (2006) and Job performance scale by Bright (2007) were used to collect data. Findings indicated the significant negative impact of job insecurity on job performance and work engagement. Furthermore, mediation Analysis through hierarchical regression analysis revealed that work engagement shows significant mediating role with job performance and job insecurity. No significant difference was shown with demographic variables such as gender, age, and years of work experience. Different strategies for the prevention of job insecurity must be focused on to increase job performance.